Technology-Based Digital Transformation in 4.0 Industrial Era (International Journal of Psychosocial Rehabilitation, 2020)
Transformation towards digitalization is motivated by the growth of small and medium enterprises (SMEs) producing creative products. Nonetheless, if this growth is not supported by a proper strategy, the SMEs may go in bankruptcy. This research aims to gain and propose a model consisting of creativity, innovation, price, and publication. This research used a snowball sampling method with 150 respondents and utilized Structural Equation Modeling (SEM) for the analysis. The results of this research show that several indicators contributing to the creativity of leather products are art and technological touch. Innovation in creating a new product, process improvement, product development, and pricing strategy should consider the costs incurred in the production. Besides, the publication is highly required in any activity involving the customers. The 4.0 industrial revolution has motivated the SMEs to improve their business process, quality of raw materials, and human resources. This study is expected to contribute to the literature in economics and management, especially related to the creativity, innovation, pricing strategy, and publication of the SMEs.